INTEGRATED ASSESSMENT OF CHP SYSTEM UNDER DIFFERENT MANAGEMENT OPTIONS FOR COOPERATIVE HOUSING BLOCK IN LOW-CARBON DEMONSTRATION COMMUNITY - Liyang Fan; Weijun Gao; Zhu Wang (Lowland Technology International, 2014)
As residential energy consumption increases recently, there is greater focus of the energy conservation activities in residential sector. The combined cooling, heating and power (CHP) system, a well-known distributed energy system technology, has been paid more and more attention. In this paper, the performances of typical CHP systems are investigated for a cooperative housing block (CHB), a mixed residential development pattern recently popularized in Japan. Based on the building’s energy consumption, CHP technologies have been assumed and assessed following two design and management modes, namely heat tracking mode and electricity tracking mode. In order to obtain a comprehensive understanding of the performance of the assumed CHP systems in CHB, the system is assessed under different area functional proportion (AFP) and area social age structure (ASAS, the proportion of housing styles for different age groups). It can be proved that the cooperative use of CHP system in CHB is better than individual use in the conventional housing development. In addition, the CHP system can perform better if the urban planner properly design the function formation and consider the lifestyle of residents in different ages.